Practicality Tests of Teaching Materials on Series and Sequences using Canva Media through Realistic Mathematical Approach - Diman, Diman; Zanthy, Luvy Sylviana; Hendriana, Heris; Fitrianna, Aflich Yusnita (IKIP Siliwangi, 2024)
This research is a study that focuses on the development of realistic-based mathematics teaching materials on high school students' mathematical communication skills on sequences and series material. Research and Development (R&D) is the research used, the model to support this research is using the ADDIE model which has 5 stages in its application, the stages of analysis, design, development, implementation, and evaluation. However, the discussion in this article only extends to the practicality test which is the advanced stage of the Development stage. The instrument used in this study was a questionnaire (validation and response). Validation was carried out by material experts, ICT experts, and responses were obtained from teachers and students. Material expert validation results reached a percentage of 85.10% of the average interpretation of